2019
DOI: 10.1155/2019/4589636
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Embolism Treated with Veno-Arterial Extracorporeal Membrane Oxygenation

Abstract: Amniotic fluid embolism (AFE) is an extremely rare yet fatal obstetric emergency. AFE presents as sudden cardiovascular collapse after a breach of maternal-fetal membranes and is often complicated by severe coagulopathy. We present a case where an AFE was treated with veno-arterial extracorporeal membrane oxygenation (ECMO) to help overcome the acute cardiopulmonary insult. The use of echocardiography proved to be an invaluable tool to help guide treatment and optimal duration of ECMO in the face of severe coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In the application of ECMO in pregnant women/parturients, there are both obstetric and non-obstetric factors. In developed countries, ECMO technology has been increasingly reported in the treatment of pregnant women/parturients with acute respiratory failure, severe heart failure, postpartum hemorrhage induced cardiac arrest, pulmonary embolism, and amniotic fluid embolism [ 14 16 ]. Ong et al systematically reviewed ECMO indications of 97 pregnant women/parturients and found that adult respiratory distress syndrome (91.9%) was the most common respiratory tract indication, while pulmonary embolism (23.7%) and perinatal cardiomyopathy (16.9%) were the two most common cardiovascular indications [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the application of ECMO in pregnant women/parturients, there are both obstetric and non-obstetric factors. In developed countries, ECMO technology has been increasingly reported in the treatment of pregnant women/parturients with acute respiratory failure, severe heart failure, postpartum hemorrhage induced cardiac arrest, pulmonary embolism, and amniotic fluid embolism [ 14 16 ]. Ong et al systematically reviewed ECMO indications of 97 pregnant women/parturients and found that adult respiratory distress syndrome (91.9%) was the most common respiratory tract indication, while pulmonary embolism (23.7%) and perinatal cardiomyopathy (16.9%) were the two most common cardiovascular indications [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in our case, the patient was in severe hemodynamic compromise, DIC, requiring massive transfusion protocol and was refractory to vasopressor support going into cardiac arrest where early intervention with ECMO led to a successful outcome. Not only prompt intervention but also early weaning of ECMO is important, as complications like hemolysis, renal function impairment, intracranial hemorrhage, sepsis, and limb ischemia are directly related to the duration of the extracorporeal life support [ 14 - 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent literature, ECMO should be considered in cases requiring prolonged CPR or, after an arrest, severe ventricular dysfunction refractory to medical management. 1 Although early indication of VA-ECMO has been described in some reports, 12,13 evidence supporting the beneficial outcomes of VA-ECMO use is insufficient, making its use controversial and not routinely recommended for AFE.…”
Section: Discussionmentioning
confidence: 99%